Improved method for producing chromium-containing high permeability grain oriented electrical steels.

The production method for high permeability grain-oriented electrical steel with controlled chromium content and rapid cooling stabilizes austenite transformation, addressing manufacturing challenges and enhancing magnetic properties.

JP2025501642APending Publication Date: 2025-01-22CLEVELAND CLIFFS STEEL PROPERTIES INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024539422
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-30
Filing Date
2022-10-26
Publication Date
2025-01-22

AI Technical Summary

Technical Problem

Existing grain-oriented electrical steels face challenges in achieving high magnetic permeability and stability due to the detrimental effects of high chromium content, which complicates austenite transformation and increases manufacturing difficulties, especially with rapid cooling processes.

Method used

A method for producing high permeability grain-oriented electrical steel with up to 2% chromium, utilizing grain growth inhibitors like aluminum nitride and manganese sulfide, combined with controlled rapid cooling rates and specific chemical compositions to stabilize austenite transformation and enhance magnetic properties.

Benefits of technology

The method achieves magnetic permeability of at least 1840 at 796 A/m with improved manufacturability and reduced thermal distortions, ensuring consistent magnetic properties and reduced core losses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501642000008
    Figure 2025501642000008
  • Figure 2025501642000009
    Figure 2025501642000009
  • Figure 2025501642000010
    Figure 2025501642000010
Patent Text Reader

Abstract

A high permeability grain oriented electrical steel having a chemical composition, by weight, of 2.5%-4.5% silicon, 0.02%-0.08% carbon, 0.01%-0.05% aluminum, 0.005%-0.050% sulfur or selenium, 0.02%-0.20% manganese, 0.05%-0.20% tin, 0.05%-1% copper, 0.5%-2.0% chromium, up to 0.10% phosphorus, and up to 0.20% antimony, the balance being essentially iron and residual elements, said steel containing chromium and phosphorus in amounts such that the Cr:(P+0.25Sb) ratio is less than 80:1, or less than 50:1, or less than 30:1, which results in very stable magnetic properties in the finished steel sheet. A hot worked band constructed of such steel is annealed and, after such annealing, rapidly cooled at a rate of at least 50°C per second from 875-950°C to a temperature below 400°C prior to cold rolling to final thickness. Such steel forms a hot worked band having a thickness of 1.5-4.0 mm and has a volume resistivity of at least 50 μΩ-cm, an austenite volume fraction (γ1150°C) of at least 20%, and an isomorphous layer thickness of at least 2% of the total thickness of at least one surface of said hot worked band.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to U.S. patent application Ser. No. 17 / 566,044, filed December 30, 2021, entitled "Improved Method for the Production of High Permeability Grain Oriented Electrical Steel Containing Chromium," the disclosure of which is incorporated herein by reference. [Background technology]

[0002] Electrical steels are broadly divided into two types: non-oriented electrical steels, which are designed to provide uniform magnetic properties in all directions, and grain oriented electrical steels, which are designed to provide high volume resistivity and highly directional magnetic properties through the formation of preferential grain orientations.

[0003] Electrical steels have iron alloyed with silicon, aluminum, and other elements that impart high volume resistivity to the steel sheet and reduce core loss during AC magnetization. Non-oriented electrical steels typically contain silicon, manganese, aluminum, and other elements generally known in the art to provide high volume resistivity and low core loss. Grain-oriented electrical steels typically contain silicon, with small amounts of manganese, aluminum, and other elements added for other purposes, such as inhibiting primary grain growth, which is important for grain-oriented electrical steels, and imparting certain metallurgical characteristics important to the steel manufacturing process. Using equation (1), the effect of common alloying additions in electrical steels on the volume resistivity (ρ) of the steel, which is typically reported in microohm-centimeters (μΩ-cm), can be calculated. TIFF2025501642000001.tif19151Where %Si, %Al, %Cr, %Mn, %Cu, %Ni, %Mo, %P, and %Sn are the weight percentages of silicon, manganese, aluminum, chromium, copper, nickel, molybdenum, phosphorus, and tin, respectively, in the steel.

[0004] Grain-oriented electrical steels are differentiated by the type of grain growth inhibition utilized, the processing method, the quality of the (110)

[0001] grain orientation achieved, and the core loss of the finished steel. Grain-oriented electrical steels are typically divided into two subclasses, indicated by the magnetic permeability measured at 796 A / m or 800 A / m. Ordinary (or conventional) grain-oriented electrical steels have a permeability of at least 1780, while high-permeability grain-oriented electrical steels have a permeability of at least about 1840, and typically exceed 1880.

[0005] To obtain the desired magnetic properties in grain oriented electrical steels, the (110)

[0001] or "Goss" grain orientation is formed during the final high temperature anneal of the steel by a process commonly referred to in the art as secondary grain growth. Secondary grain growth is a process in which small cube-on-edge oriented grains grow preferentially to incorporate grains of other orientations. Active secondary grain growth depends primarily on two factors:

[0006] First, a grain growth inhibitor dispersion must be provided that is capable of suppressing primary grain growth in favor of secondary grain growth.Typical methods used to produce high permeability grain oriented electrical steels rely on precipitated aluminum nitride, or precipitated aluminum nitride in combination with precipitated manganese sulfide or precipitated copper sulfide, manganese selenide, or other nitrides such as boron, silicon, and other elements.

[0007] Second, the grain structure and crystallography of the steel, especially the surface and near surface layers of the steel surface, must provide suitable conditions for secondary grain growth. The properties of the surface and near surface layers of the steel surface of the hot processed band are important for the development of high permeability grain oriented electrical steels. This surface region is carbon depleted and substantially free of austenite and its decomposition products, forming a substantially single phase, or isomorphous, ferritic microstructure, which is referred to in the art as the surface decarburized layer. In contrast, the interior microstructure of the hot worked band is polymorphous with mixed phases of ferrite, austenite, or austenite decomposition products. The boundaries between these surface and interior layers are commonly referred to in the art as shear bands. The appropriate thickness, microstructure, and composition of the shear bands are conducive to the development of Goss orientation, since nucleation grains most likely to produce vigorous secondary grain growth with a high degree of cube-on-edge grain orientation are found within the isomorphous layer and near the boundary between the surface isomorphous layer and the interior polymorphous layer.

[0008] The amount of ferrite and austenite is also important in producing high permeability grain oriented electrical steels. Such steels typically contain at least 20% austenite, and in some cases typically 25-55% austenite, and in other cases 35-45% austenite. During the annealing process, the austenite promotes the dissolution and precipitation of aluminum nitride, which transforms on cooling to hard second phases such as martensite, bainite, and retained austenite. The formation of such hard phases occurs approximately after the cold rolled strip has been subjected to a recrystallization anneal, such as during a decarburization anneal. <111> It is important for the development of fiber texture and for the development of cube-on-edge nuclei at the boundary between isomorphous and polymorphous phases. Equation (2) below is used to calculate the peak austenite volume fraction (γ1150°C) at 1150°C for steels containing approximately 3.0-3.6% silicon, 0.02-0.08% carbon, and up to 2.0% chromium. TIFF2025501642000002.tif19167

[0009] Using this formula, gamma 1150°C is calculated using the weight percentages of carbon, manganese, phosphorus, sulfur, silicon, chromium, nickel, molybdenum, copper, aluminum, and nitrogen contained in the steel.

[0010] Prior art grain oriented electrical steels typically contain silicon levels between 2.95% and 3.45%, providing a volume resistivity of about 45-50 μΩ-cm using formula (1). These high silicon levels have long been known to cause physical manufacturing problems due to reduced ductility, increased brittleness, and increased sensitivity to processing temperatures, all of which affect manufacturing difficulty and cost. The use of such high levels of silicon typically requires that the levels of austenite forming elements are also high to maintain the proper proportion of austenite and ferrite in the steel, i.e., phase balance. The most common addition to increase the level of austenite is carbon. High levels of silicon and carbon typically reduce the solidus temperature, which has a significant effect on the formation of defects that may occur during high temperature processing, such as solidification, casting of slabs or strip, reheating of slabs or strip, and / or hot rolling. Additionally, higher silicon and carbon levels can adversely affect physical ductility and brittleness, make cold rolling more difficult, and increase the time required to remove carbon during decarburization annealing. As a result, the technical difficulty of processing the steel material and the manufacturing costs increase.

[0011] Chromium additions are used to increase volume resistivity, promote the formation of austenite, and provide other beneficial properties in the manufacture of grain oriented electrical steels. The use of chromium additives in the production of grain oriented electrical steels is shown in U.S. Patent No. 5,421,911, entitled "Regular Grain Oriented Electrical Steel Production Process," issued on June 6, 1995, U.S. Patent No. 5,702,539, entitled "Method for Producing Silicon-Chromium Grain Oriented Electrical Steel," issued on December 30, 1997, U.S. Patent No. 7,887,645, entitled "High Permeability Grain Oriented Electrical Steel," issued on February 15, 2011, and U.S. Patent No. 9,881,720, entitled "Grain Oriented Electrical Steel with Improved Forsterite Coating Characteristics," the contents of each of these three patents being incorporated herein by reference.

[0012] In industrial practice, chromium additions of 0.10% to 0.40% have been employed, with typical additions being 0.20% to 0.35%. Steels with chromium contents of 0.30% to 0.35% are known to consistently yield both good physical processing and magnetic properties, provided that the conditions of composition, austenite-ferrite phase balance, isomorphous layer thickness, and cooling after annealing prior to final cold rolling are met. The amount of austenite formed during the annealing process and the transformation of austenite to form "hard phases", i.e. martensite, retained austenite, bainite and / or similar phases, during cooling after the annealing process and prior to cold rolling to final thickness must be controlled. However, above a level of 0.50%, control of the austenite transformation can become increasingly difficult, especially above 0.75% chromium. As the chromium content increases, the transformation of austenite to desirable "hard phases" after annealing and rapid cooling processes decreases, and phases such as ferrite, cementite, pearlite (ferrite-cementite aggregates) or mixtures thereof may form, resulting in increasingly poor and irregular development of the (110)

[0001] grain orientation required for good magnetic properties in the finished steel. As a result, industrial practice has limited the chromium content to a maximum of about 0.40%. Summary of the Invention [Means for solving the problem]

[0013] High permeability grain oriented electrical steels containing up to 2% chromium with excellent mechanical and magnetic properties are produced using grain growth inhibitors comprising primarily aluminum nitride alone or in combination with one or more of manganese sulfide, manganese selenide, or other inhibitors. Hot worked band having a thickness of 1.5-4.0 mm has a chemical composition, in weight percent, of 2.5%-4.5% silicon, 0.02%-0.08% carbon, 0.01%-0.05% aluminum, 0.005%-0.050% sulfur or selenium, 0.02%-0.20% manganese, 0.05%-0.20% tin, 0.05%-1% copper, 0.5%-2.0% chromium, up to 0.10% phosphorus, and up to 0.20% antimony, with the remainder essentially being iron and residual elements incidental to the steel making process. In this application, the term "band" is used generally to identify the steel product after hot rolling and before any annealing prior to cold rolling, and the term "strip" is used generally to identify the steel product after such annealing. The steels contain chromium and phosphorus / antimony in amounts such that the Cr:[P+(0.25Sb)] ratio is less than 80:1, less than 50:1, or less than 30:1 to ensure stable magnetic properties and better manufacturability of the finished steel sheet. In certain embodiments, such steels are rapidly cooled at a rate of greater than 50° C. per second, greater than 60° C. per second, or greater than 70° C. per second after annealing of the hot rolled steel.

[0014] The high permeability grain oriented electrical steel of the present invention has a volume resistivity of at least 50 μΩ-cm, and the hot worked band has an austenite fraction (γ1150°C) of at least 20% and an isomorphous layer thickness of at least 2% of the total thickness on at least one surface of the hot worked band, the band having a thickness of 1.5 to 4.0 mm. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 shows a photograph of the resulting microstructure after annealing and rapid cooling at 60° C. per second from 940° F. to 340° F. [Diagram 2] FIG. 2 is a graph showing the relationship between magnetic permeability at 796 A / m and Cr:[P+(0.25Sb)] ratio for the steel of Example 3. [Diagram 3] FIG. 3 is a graph showing the relationship between iron loss at 1.7 T, 60 Hz and the Cr:[P+(0.25Sb)] ratio for the steel of Example 3. [Figure 4] FIG. 4 is a graph showing the relationship between magnetic permeability at 796 A / m and Cr:[P+(0.25Sb)] ratio for the steel of Example 4. [Diagram 5] FIG. 5 is a graph showing the relationship between iron loss at 1.7 T, 60 Hz and the Cr:[P+(0.25Sb)] ratio for the steel of Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The high permeability grain oriented electrical steel of the present invention allows for the addition of higher levels of chromium to obtain its positive effects while reducing the detrimental effect of chromium on the efficient transformation of austenite to a hard second phase. The steel thus has a permeability measured at 796 A / m of at least 1840. The steel of the present invention has 2.5% to 4.5% silicon, 0.5% to 2.0% chromium, 0.02% to 0.08% carbon, 0.01% to 0.05% aluminum, 0.005% to 0.012% nitrogen, 0.005% to 0.050% sulfur or selenium, 0.02% to 0.20% manganese, 0.05% to 0.20% tin, 0.05% to 1% copper, up to 0.10% phosphorus, and up to 0.20% antimony, the remainder being essentially residual elements incidental to the iron and steel making process.

[0017] Silicon is added to the melt primarily to improve core loss by increasing the volume resistivity. In addition, silicon promotes the formation and / or stabilization of ferrite, and thus silicon is one of the major elements influencing the volume fraction of austenite. Higher silicon is desirable to improve magnetic qualities, but its effects must be considered to maintain the desired phase balance, microstructural characteristics, and mechanical properties. In the steels of the present invention, silicon is present, by weight percent, in an amount of 2.5% to 4.5%, in some cases in an amount of 2.75% to 3.75%, or in other cases in an amount of 2.90% to 3.50%.

[0018] Chromium is added to the melt to improve core loss by increasing the volume resistivity which helps to lower the core loss of the steel of the present invention. However, chromium has other effects on the austenite-ferrite phase balance and the formation of some desirable properties which must be considered. While chromium promotes the formation of austenite, higher amounts of chromium affect austenite decomposition during cooling in the steel of the present invention. In the steel of the present invention, chromium is present in an amount of 0.5% to 2.0%, or in some cases in an amount of 0.6% to 1.8%, and in other cases in an amount of 0.7% to 1.7%, by weight. Steels containing more than 2.0% chromium have problems with decarburization annealing and it has become increasingly difficult to achieve carbon final levels below 0.003% to prevent magnetic aging.

[0019] Carbon is added to the melt primarily to promote the formation and / or stabilization of austenite, and is therefore one of the elements that influence the volume fraction of austenite (γ1150°C). Carbon concentrations less than 0.02% immediately prior to cold reduction to intermediate thickness are undesirable because they destabilize secondary recrystallization and impair the quality of the cube-on-edge orientation of the product. High carbon contents above 0.08% are undesirable because they can cause isomorphous layer thinning, thereby weakening secondary grain growth and resulting in poor cube-on-edge orientation and difficulty in decarburizing the strip to carbon levels below 0.003% required to prevent magnetic aging. In the steels of the present invention, carbon is present in the melt and hot band in an amount of 0.02% to 0.08%, or in some cases 0.03% to 0.07%, or in other cases 0.04% to 0.06%, by weight.

[0020] Aluminum is added to the melt to combine with nitrogen to form precipitated aluminum nitrides necessary to inhibit primary grain growth and to support stable and vigorous secondary grain growth. Aluminum also helps to control the amount of dissolved oxygen in the steel melt, but the percentage of soluble aluminum must be maintained within upper and lower limits. In the steels of this invention, soluble aluminum is present in an amount of 0.01% to 0.05%, or in some cases 0.015% to 0.040%, or in other cases 0.020% to 0.035%, by weight.

[0021] Nitrogen is added to the melt to combine with aluminum to form precipitated aluminum nitrides necessary for primary grain growth inhibition and to support stable and vigorous secondary grain growth. In the steels of the present invention, nitrogen is present in an amount of 0.005% to 0.0120%, or in some cases 0.008% to 0.011%, or in other cases 0.009% to 0.010%, by weight. In other embodiments, a strip nitriding treatment can be used to increase the nitrogen level of the strip prior to high temperature annealing. In the practice of this method, the combined level of nitrogen provided in the melt and by nitriding is in the range of 0.0120% to 0.030%.

[0022] Sulfur and selenium can be added to the melt to combine with manganese to form precipitated manganese sulfides and / or precipitated manganese selenides necessary for primary grain growth inhibition. In the steels of the invention, sulfur is present in an amount of 0.005% to 0.050%, or in some cases 0.015% to 0.035%, by weight. Some or all of the sulfur in the steels of the invention can be replaced by selenium, with the total amount of sulfur and selenium or selenium alone being present in an amount of 0.005% to 0.050%, or in some cases 0.015% to 0.035%, by weight.

[0023] Manganese is added to the melt to combine with sulfur to form precipitated manganese sulfides and / or precipitated manganese selenides necessary for primary grain growth inhibition. When using conventional steel melting and casting methods, in which continuously cast slabs are used to produce the initial band for processing according to the method of the present invention, it is advantageous to have a low proportion of excess manganese, i.e., manganese not combined as manganese sulfides or manganese selenides, to facilitate dissolution of the manganese sulfides during reheating of the slab prior to hot rolling. In the steels of the present invention, manganese is present in an amount of 0.02% to 0.20%, or in some cases 0.03% to 0.12%, or in other cases 0.04% to 0.08%, by weight.

[0024] Tin is added to the melt to enhance the function of aluminum nitride and other grain growth inhibitors. In the steels of the present invention, tin is present in an amount of 0.03% to 0.25%, or in some cases 0.05% to 0.20%, and in other cases 0.10% to 0.15%, by weight. Tin levels below 0.03% are insufficient to enhance the quality of the grain growth inhibitor, while levels above 0.25% may interfere with carbon removal during pickling and decarburization annealing prior to cold rolling.

[0025] Copper is added to the melt to enhance the core loss of the steel by promoting the formation of the forsterite film and reducing the size of the (110)

[0001] grains that form in the finished steel. In the steels of this invention, copper is present in an amount of 0.03% to 1.0% by weight, or in some cases in an amount of 0.05% to 0.45% by weight, or in other cases in an amount of 0.10% to 0.30% by weight. Copper levels below 0.03% are insufficient to enhance the quality of the forsterite film, while levels above 1.0% may interfere with carbon removal during pickling and decarburization annealing prior to cold rolling.

[0026] Phosphorus is added to the melt primarily to enhance the workability of the steel of the invention, and secondarily, phosphorus serves to increase the volume resistivity of said steel. The addition of phosphorus helps to control the austenite transformation process by promoting the formation of technologically useful "hard phases" and inhibiting the formation of cementite. In the steel of the invention, phosphorus is present in an amount of up to 0.10% by weight, or in some cases in an amount of 0.015% to 0.065% by weight, or in other cases in an amount of 0.020% to 0.045% by weight. Phosphorus levels below 0.005% are insufficient to control austenite decomposition, while levels above 0.10% may reduce the mechanical quality of the steel during cold rolling and slow carbon removal during decarburization annealing.

[0027] Antimony acts similarly to phosphorus in influencing the austenite transformation process and the formation of cementite. In the steels of the present invention, antimony is present in an amount of up to 0.2% by weight, or in some cases in an amount of 0.015% to 0.15%, and in other cases in an amount of 0% to 0.014%.

[0028] In the steels of the present invention, the chromium and phosphorus and / or antimony are measured in weight percent, but are used in amounts appropriate to control the austenite transformation during cooling to "hard phases", e.g., martensite, retained austenite, bainite, etc., necessary to achieve high quality (110)

[0001] grain orientation in the finished steel plate. Thus, in the steels of the present invention, the Cr:P ratio must be less than 80:1, or less than 50:1, or less than 30:1. Furthermore, it is believed that antimony functions similarly in place of or in addition to phosphorus, where the ratio is expressed as Cr:[P+(0.25Sb)]. In the steels of the present invention, the chromium, phosphorus, and antimony used must have a Cr:[P+(0.25Sb)] ratio of less than 80:1, or less than 50:1, or less than 30:1.

[0029] The remainder of the steel comprises iron and residual elements incidental to the steelmaking process.

[0030] The high permeability grain oriented electrical steel of the present invention can be produced in many ways. The band can be produced from an ingot, a slab produced from an ingot, or a continuously cast slab, which are reheated to 1100°-1400°C and then hot rolled to provide an initial hot worked band of thickness 1.5-4.0 mm. The method of the present invention is also applicable to bands produced by a method of providing a continuously cast slab or a slab produced from an ingot with little heating, or by a method of directly casting the molten metal into a band suitable for further processing. However, in some cases, the equipment capacity may be insufficient to provide an initial hot worked band having a thickness suitable for the steel of the present invention, and a cold reduction of up to 30% or a hot reduction of up to 80% may be applied to provide a suitable thickness before annealing the hot worked band.

[0031] The hot worked band is annealed at 1100°C-1200°C for a time sufficient for complete austenite formation. Carbon losses may occur during annealing, and adjustments to the melt composition may be required to maintain the desired austenite-ferrite phase balance. Furthermore, such carbon losses may be affected by the amount of silicon and chromium in the steel, the thickness of the initial strip, the oxidation potential of the annealing atmosphere, and / or the time and temperature of annealing. After annealing, the strip may be cooled at a rate of 10-20°C per second to a temperature of 875-975°C, and then rapidly cooled to below 400°C. The annealed strip is rapidly cooled at a rate of greater than 50°C per second, or in some cases greater than 60°C per second, or in other cases greater than 70°C per second. Such rapid cooling is effective to control the austenite transformation to the hard second phase desired for the steel of the present invention. The strip is then air cooled from 400°C to ambient temperature.

[0032] In the prior art high permeability grain oriented steels, it has been difficult to achieve the very rapid cooling required to obtain a highly uniform microstructure across the strip width. In particular, the use of very rapid cooling leads to distortions in the flatness of the strip, which leads to strong temperature non-uniformities across the strip width, complicating further processing, especially the cold rolling step. Furthermore, this leads to a final product with a large variation in magnetic properties, which has been a barrier to the use of chromium levels above 0.50%. It has been found that the steel of the present invention offers strong control of the austenitic transformation using rapid cooling. As a result, the thermal distortion of the strip is reduced, producing an annealed strip with a very uniform microstructure. Furthermore, the final product has the superior magnetic properties obtained with chromium levels above 0.50%.

[0033] The steel may be cold reduced in one or more stages separated by annealing steps to provide a cold reduction of at least 80% to the cold rolled strip prior to decarburization annealing. After cold reduction to final thickness is complete, the steel is subjected to a decarburization annealing step to reduce the carbon content to an amount that minimizes magnetic aging, typically less than 0.003%, using a wet hydrogen-containing atmosphere such as pure hydrogen or a mixture of hydrogen and nitrogen having a nominal H2O / H2 ratio of 0.35 to 0.55. The soak temperature for the decarburization annealing step is at least 800°C, or in some cases at least 830°C. The decarburization annealing step of the steel of the present invention may be performed by rapidly heating the steel from a temperature of 450°C or less to a temperature of 740°C or more at a rate of more than 500°C per second, although the decarburization annealing step does not require such rapid heating rates. During or after the decarburization annealing, the strip may be optionally subjected to a nitriding treatment. The decarburization anneal further prepares the steel for the formation of a forsterite or "mill glass" film in a high temperature final anneal by reaction of the surface oxide film with an annealing separator comprising primarily magnesium oxide and optionally small amounts of titanium oxide, boron-containing or chlorine-containing additives.

[0034] The magnesia-coated coil is then subjected to an extended anneal at high temperatures of 1100°C to 1200°C in a H2-N2 atmosphere during which the (110)

[0001] grain orientation develops and a forsterite or "mill glass" coating forms on the surface of the steel, after which the steel is refined by annealing in 100% H2 such that elements such as sulfur, selenium, and nitrogen are substantially removed. This final high temperature anneal is necessary to develop the cube-on-edge grain orientation. Typical annealing conditions use a heating rate of less than 80°C per hour to 815°C, and then further heating at a rate of less than 50°C per hour until secondary grain growth is complete. Once secondary grain growth is complete, the steel is held at the soak temperature for at least 5 hours, and in some cases at least 20 hours, to remove the nitrogen, sulfur, and / or selenium used as primary grain growth inhibitors and refine the finished steel.

[0035] After completion of the high temperature anneal, the coil is cooled and uncoiled, cleaned to remove any residue from the magnesia separator coating, and typically a C-5 insulation coating is applied over the forsterite coating and the steel is heat flattened. It is common practice to apply some domain refinement measures to further reduce core losses in the high permeability grain oriented electrical steel product, but such additional processing is not required.

[0036] Example 1 A series of industrial heats having exemplary melt compositions of the prior art and high permeability grain oriented electrical steels of the present invention are summarized in Table 1. Heats A-D had compositions representative of prior art steels with 0.010% phosphorus or less and at chromium contents greater than 0.50% resulted in Cr:[P+(0.25Sb)] ratios greater than 50:1, while heats E-G were examples of the high permeability grain oriented steels of the present invention having chromium contents of 0.50% or more and sufficient phosphorus content to result in Cr:[P+(0.25Sb)] ratios of 45:1 or less. TIFF2025501642000003.tif56169

[0037] After melting, the steel was continuously cast into slabs of 200 mm thickness, heated to 1000-1100°C, reduced to a thickness of 150 mm, further heated to 1375-1400°C, and hot rolled to an initial hot rolled band thickness of 2.0 mm. The hot rolled coils were processed in a plant where they were continuously strip annealed at a nominal temperature of 1150°C for a time sufficient for complete austenite formation, air cooled at a nominal rate of 10-15°C per second to a nominal temperature of 940°C, subsequently rapidly cooled at a nominal rate of 60°C per second to 340°C, and finally cooled to room temperature in ambient air.

[0038] After chemical etching, the microstructures were examined using optical metallography for phase identification, as shown in Figure 1. Heat treatments B, C, and D show that as the chromium content increased, the austenite transformation process resulted in an increase in the amount of pearlite and / or ferrite and a decrease in the amount of "hard phases." In contrast, heat treatments E, F, and G show that a consistent and efficient process of austenite decomposition was obtained, resulting in a very uniform formation of the desired "hard phases" in steels containing up to 1.66% chromium.

[0039] Example 2 A series of heat treatments were melted to chromium levels ranging from 0.65% to 1.51%, as shown in Table 2. Heat treatments H and I are prior art compositions with residual phosphorus levels of 0.009% and Cr:[P+(0.25Sb)] ratios of 73:1 or greater, while heat treatments J through N are exemplary compositions of the high permeability grain oriented steels of the present invention with phosphorus additions resulting in Cr:[P+(0.25Sb)] ratios of 40:1 or less. TIFF2025501642000004.tif54168

[0040] The steel was continuously cast into slabs and processed by hot rolling in a manner identical to the process of Example 1. Samples were taken from the hot rolled coils for laboratory studies where they were annealed at a nominal temperature of 1150°C for a time sufficient for complete austenite formation, air cooled at a rate of 10-15°C per second to a temperature of 940°C, and then rapidly cooled at rates of 39, 50, 61, 67, 72, 78, and 83°C per second to a temperature below 100°C. The microstructures after annealing and rapid cooling were examined by optical micrographs after chemical etching for phase identification. The results are summarized in Table 3. TIFF2025501642000005.tif85170

[0041] Heat Treatments H and I, with chromium contents between 0.65% and 0.89%, gave poor microstructures when cooled rapidly at 30-50°C per second, but more acceptable microstructures were obtained when heat treatment H was cooled at rates above 72°C per second, and heat treatment I was cooled at rates above 78°C per second. However, such aggressive cooling distorted the flatness of the strip and caused temperature inhomogeneities during cooling, which in turn resulted in inhomogeneous microstructures in the finished steel and altered magnetic properties. In contrast, heat treatments J-N of the high permeability grain oriented steels of the present invention, with Cr:[P+(0.25Sb)] ratios of 40:1 or less, gave consistently excellent results over the entire range of cooling rates due to improved control of the austenite transformation process, with very consistent "hard phase" formation using only a moderately high cooling rate of 60°C per second.

[0042] Example 3 A series of industrial heat treats containing 0.64-0.68% chromium were melted with exemplary compositions of the prior art and high permeability grain oriented steels of the present invention, as shown in Table 4. Heat treats O, P, and Q have compositions representative of prior art steels with residual phosphorus levels of 0.008%-0.009%. Heat treats R-V, having exemplary compositions of the high permeability grain oriented steels of the present invention, contained up to 0.040% phosphorus with Cr:[P+(0.25Sb)] ratios less than 50:1. TIFF2025501642000006.tif57170

[0043] All heat treated materials were continuously cast into slabs and processed by hot rolling, strip annealing, and rapid cooling according to the method described in Example 1. The annealed and rapidly cooled strips were cold rolled to a final thickness of 0.27 mm and decarburized annealed. The decarburization annealing process consisted of heating the strip at a rate of over 500°C per second to a temperature of 740°C, and then conventionally heated to a soak temperature of 815°C in a moist hydrogen-nitrogen atmosphere with a nominal H2O / H2 ratio of 0.35-0.45 for approximately 120 seconds, sufficient to reduce the carbon level in the steel to below 0.002%. The decarburized strip was coated with an MgO anneal separator coating containing 5% TiO2 and other additions, dried, and coiled. The coils were final annealed by heating them in a 25% nitrogen, 75% hydrogen atmosphere to a nominal soak temperature of 1200°C, after which the steel was held in 100% dry hydrogen for at least 15 hours for secondary grain growth and refinement. The coils were then unwound and cleaned to remove excess MgO, coated with a secondary coating, thermally flattened at a temperature of 850°C, and laser scribed after thermal flattening was completed. After processing was completed, test specimens were cut from the leading and trailing ends of each coil and tested for permeability at 796A / m and core loss at 1.7T 60Hz using the Epstein test method of ASTM A343. The thermal average and worst test values ​​of permeability and core loss versus Cr:[P+(0.25Sb)] ratio are shown in Figures 2 and 3, respectively.

[0044] As shown in Figures 2 and 3, for steels with chromium contents between 0.65% and 0.70%, the magnetic permeability is consistently high and the core loss is consistently low when the Cr:[P+(0.25Sb)] ratio is within the range of the method of the present invention. The appearance and technical properties of the forsterite coating formed on the product were excellent.

[0045] Example 4 A series of industrial heat treats containing 0.89-1.07% chromium were melted with exemplary compositions of the prior art and the present invention, as shown in Table 5. Heat treats W-AB are prior art steel compositions with typical residual phosphorus levels of 0.008%-0.009%, resulting in Cr:[P+(0.25Sb)] ratios of 80:1 or greater. Heat treats AC-AG are high permeability grain oriented steel compositions of the present invention with as much as 0.040% phosphorus, resulting in Cr:[P+(0.25Sb)] ratios of 35:1 or less. TIFF2025501642000007.tif72170

[0046] All heat treatments were continuously cast into slabs and processed as described in Example 3, except that the steel was cold rolled to a final gauge of 0.23 mm. After processing was completed, test specimens were cut from the head and tail of each coil and tested for permeability at 796 A / m and core loss at 1.7 T 60 Hz using the Epstein test method of ASTM A343. The thermal average and worst test values ​​of permeability and core loss versus Cr:[P+(0.25Sb)] ratio are shown in Figures 4 and 5, respectively.

[0047] As shown in Figure 4, the method of the present invention significantly improved the product consistency and magnetic permeability for steels with chromium contents between 0.90% and 1.1%. Core loss was improved due to the high volume resistivity resulting from the high chromium content and advanced grain orientation achieved using the method of the present invention. Furthermore, the physical appearance and technical properties of the forsterite coating formed on the product were found to be excellent.

Claims

1. A high permeability grain oriented electrical steel hot band having, by weight, 2.5% to 4.5% silicon, 0.02% to 0.08% carbon, 0.01% to 0.05% aluminum, 0.005% to 0.012% nitrogen, 0.005% to 0.050% sulfur or selenium, 0.02% to 0.20% manganese, 0.05% to 0.25% tin, 0.05% to 1% copper, 0.5% to 2.0% chromium, up to 0.10% phosphorus, and up to 0.5% tin. 20% antimony with the remainder essentially being iron and residual elements, the ratio of weight percent chromium to [weight percent phosphorus plus 0.25 times weight percent antimony] being less than 80:1, said band having a thickness of about 1.5 to about 4 mm, a volume resistivity of 50 μΩ-cm or greater, and an austenite volume fraction (γ1150°C) of at least about 20%.

2. 2. The high permeability grain oriented electrical steel hot band of claim 1, having 0.6% to 1.8% chromium by weight.

3. 2. The high permeability grain oriented electrical steel hot band of claim 1, having, by weight, 0.7% to 1.7% chromium.

4. 2. The high permeability grain oriented electrical steel hot band of claim 1, having, by weight, 0.015% to 0.065% phosphorus.

5. 2. The high permeability grain oriented electrical steel hot band of claim 1, having, by weight, 0.020% to 0.045% phosphorus.

6. 2. The high permeability grain oriented electrical steel hot band of claim 1, wherein the ratio of weight percent chromium to [weight percent phosphorus plus 0.25 weight percent antimony] is less than 50:

1.

7. 2. The high permeability grain oriented electrical steel hot band of claim 1, wherein the ratio of the weight percent of chromium to the weight percent of phosphorus plus 0.25 times the weight percent of antimony is less than 30:

1.

8. 10. The high permeability grain oriented electrical steel hot band of claim 1 having no intentionally added antimony and a ratio of weight percent chromium to weight percent phosphorus of less than 80:

1.

9. 10. The high permeability grain oriented electrical steel hot band of claim 1 having no intentionally added antimony and a ratio of weight percent chromium to weight percent phosphorus of less than 50:

1.

10. 10. The high permeability grain oriented electrical steel hot band of claim 1 having no intentionally added antimony and having a ratio of weight percent chromium to weight percent phosphorus of less than 30:

1.

11. A method for producing high permeability grain-oriented electrical steel, comprising the steps of: Providing a hot band according to claim 1; annealing the band at a temperature of 1100°C to 1200°C for 10 seconds to 10 minutes to form a strip prior to final cold rolling, and then rapidly cooling the annealed strip at a rate of greater than 50°C per second; cold rolling the cooled and annealed strip in one or more stages, thereby providing a cold reduction of at least 80% to said cold rolled strip prior to a decarburization anneal; decarburization annealing the cold rolled strip; coating at least one surface of the decarburization annealed strip with an annealing separator coating; final annealing the coated strip; The method according to claim 1,

12. 12. The method of claim 11, wherein the rapid cooling of the annealed strip occurs at a rate of greater than 60°C per second.

13. 12. The method of claim 11, wherein the rapid cooling of the annealed strip occurs at a rate of greater than 70°C per second.

Citation Information

Patent Citations

  • Grain-directional silicon steel having high volume resistivity

    JP1997118964A

  • Grain oriented silicon steel sheet excellent in coating film characteristic and magnetic property and its production

    JP2000355717A

  • Grain-oriented electromagnetic steel sheet with low iron loss and manufacturing method therefor

    JP2002220642A

  • High permeability grain oriented electrical steel

    JP2013100602A

  • Low iron loss directional electromagnetic steel sheet and manufacturing method therefor

    JP2019119933A